Risk Factors for Voice Disorders in Undergraduate Speech Language Pathology Students - Kyriakou, Kyriaki; Theodorou, Elena; Petinou, Kakia; Phinikettos, Ioannis (My University, 2024)
Objectives: The aim of this research study is to determine the risk factors for voice disorders in SLP students in order to help us develop specific goals for a vocal hygiene education program specifically for SLP students. Methods: An online questionnaire was completed by 121 undergraduate SLP students. Participants were divided into two groups, students with no self-perceived voice disorders (NVD group) and students with self-perceived voice disorders (VD group). The Fisher Exact test (FET) was used to explore the differences in responses for each voice risk factor and the academic and occupational consequences between students with and without self-perceived voice disorders. Results: Students in the VD group were more likely to experience vocal fold problems, hearing problems and throat clearing than in the NVD group. More students in the VD group reported to “sometimes’ and “often” take medications that impact their voice, hear a “moderate” amount of noise generated from the passage of planes and the road and hear a “moderate” and “large” amount of noise generated within and outside the building than in the NVD group. Moreover, students in the VD group were more likely to limit their ability to perform certain tasks at school (eg, participating in lectures) and clinical practicum (eg, administering therapy sessions) and reduce their interactions annually due to voice problems. Conclusions: Health, voice use, lifestyle, and environmental factors are risk factors for voice disorders that were presented more frequently in SLP students with self-perceived voice disorders.
Keywords: Risk factors; Students; Voice disorders; Speech language pathology